Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

Show that the sum of 5th term from beginning and 5th term from the end of an A.P is equal to the sum of the 1st and last term.​

Sagot :

Answer:

Step-by-step explanation:

formulae for AP

sum of n terms in AP, Sn = [tex]\frac{n}{2\\}[/tex] [2a+(n-1)d]

nth term of AP, aₙ=a₁ + (n-1) d

let there be 6 terms in an AP

the first term be a₁ and so the difference be d

then the 5th term from the beginning will be a₅=a₁ + (5-1) d = a₁ + 4d

and 5th term from the last i.e a₂=a₁+d

sum of 5th term from beginning and 5th term from the last be (a₅ and a₂ respectively), = (a₁ + 4d)+(a₁+d) = 2a₁+5d

sum of 1st and last term is (a₁+a₆) =a₁+(a₁ + 5d) = 2a₁+5d

hence proved.